Retracted: INTEGRASI PAJAK DAN ZAKAT DI INDONESIA PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF - Moh. Abdur Rohman Wahid (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2016)
This paper was retracted by Fakultas Ekonomi dan Bisnis Islam as Publisher on August 8, 2019. This paper was published due to a technical error and was not intended to be included in this journal. This article is the property of Masnun Tahir & Zasiana Elly Triantini, which has been published in the journal Al-Adalah Faculty of Sharia UIN Raden Intan Lampung volume 12 number 1 in 2015 at http://ejournal.radenintan.ac.id/index.php/adalah/article/view/204/374. Thus the article belongs to Moh. Abdur Rohman Wahid was not published by us. Retractions are published on August 8, 2019. Tulisan ini menawarkan konsep integrasi pajak dan zakat sebagai bentuk semangat baru dalam meningkatkan zakat dan pajak di Indonesia. Integrasi zakat dan pajak penting untuk diupayakan karena pertumbuhan zakat semakin meningkat dari waktu ke waktu yang ditandai dengan makin meningkatnya jumlah Badan Amil Zakat dan nomor akuisisi sedekah dari tahun ke tahun. Selain dari itu, perkembangan kekayaan serta kualitas pelayanan pengembangan distribusi zakat wajib, termasuk pemanfaatannya, menunjukkan trend yang terus meningkat secara progresif. Dengan pertumbuhan yang signifikan ini, zakat dapat menjadi alat kesejahteraan ekonomi dan sosial bagi umat dan kedudukannya sama penting dengan pajak penghasilan negara. Pajak dan zakat, bilamana diintegrasikan dalam suatu konsep dan aturan hukum yang jelas, diyakini dapat memajukan perekonomian Indonesia. This paper propose the concept of integration between taxes and zakat to accelerate the achievement of social welfare in Indonesia. The integration is important as the growth of zakat steadily increases from time to time which is marked by the increasing number of Amil Zakat and alms acquisition from year to year. At the same time, the development of wealth and the service quality of obligatory zakat distributions, including utilization, is also increases progressively. Undoubtly, with this significant growth, charity, like the tax, can be utilized as a tool to achieve social walfare as well as to improve the economy of Indonesia.